Rediscovery of Kurian’s types of Hymenoptera at Forest Research Institute, Dehradun, India with notes on Indian bethylid fauna - Singh, Sudhir; Colombo, Wesley D.; Shreevihar, Santhosh; Faisal, Mohd.; Pandey, Vijay P.; Tribull, Carly M. (Zootaxa, 2021)
The types specimens of many taxa described by Chandy Kurian were considered lost for many years, which prevented the recognition of the species delimited by him. Fifty holotypes have been rediscovered in the National Forest Insect Collection of Forest Research Institute, Dehradun, Uttarakhand, India. Forty-five types belong to Bethylidae (Cephalonomia tritici, Chlorepyris biharina, C. mackenziei, C. pusana, C. sanctipauli, Epyris agraensis, E. agrensis, E. bombayensis, E. delhiensis, E. duni, E. duttai, E. indicae, E. manii, E. patnae, E. pusae, E. shishami, Goniozus ahmeadi, G. chatterjii, G. chowdhari, G. hybleae, G. lygropiae, G. madrassippattanami, G. marasmi, G. mori, G. morindae, G. nephoterycis, G. nilamburensis, G. pulveriae, G. salvadorae, G. sanctijohannis, G. thalasodi, Laelius agraensis, Odontepyris argyriae, O. batrae, O. cirphi, O. hypsipylae, O. indicus, Pristepyris agraensis, Pristocera govindrami, Sclerodermus delhiensis, Sc. hardwickiae, Sc. mori, Sc. raonis, Sulcomesitius bahaduri and Su. duni), one to Chrysididae (Lustrina assamensis), three to Dryinidae (Lestodryinus guptai, Neodryinus karnalensis and N. pusae) and one to Formicidae (Neoclystopsenella luffae). Six new combinations are proposed: Epyris mackenziei comb. nov. from Chlorepyris; Formosiepyris agraensis comb. nov. from Epyris; Holepyris raonis comb. nov. from Sclerodermus; Holepyris patnae comb. nov. from Epyris; Pristocera agraensis comb. nov. from Pristepyris; and Trachepyris sanctipauli comb. nov. from Chlorepyris. We also provide updated diagnoses, as well as detailed remarks and photographs for all types rediscovered. In addition, we provide researchers worldwide with valuable taxonomic information for the Bethylidae, Chrysididae, Dryinidae and Formicidae described by Kurian. A review of Bethylidae from India and a tribute to Chandy Kurian has also been provided.